Efficacy and safety of minimally invasive axial presacral L5-S1 interbody fusion in the treatment of lumbosacral spine pathology: a retrospective clinical and radiographic analysis : Minimally invasive axial presacral L5-S1 interbody fusion - Balsano, Massimo; Spina, Mauro; Segalla, Sara; Michele, Da Broi; Doria, Carlo (Acta Biomedica Atenei Parmensis, 2020)
BackgroundThe surgical treatment of degenerative disc disease L5-S1 is considerably controversial. The purpose of this study was to evaluate the radiographic and clinical results of patients treated with AxiaLif® Technique (AxiaLif®, AMSGroup, Italy) using a minimally invasive pre-sacral approach.MethodsFrom 2013 to 2018 a total of 52 patients have been treated (12 M, 40 F; mean age 46.3 years). Diagnosis included L5 isthmic spondylolisthesis low-grade dysplasia, primary and secondary degenerative disc disease. 43 patients have been followed for at least 2 years. Fusion assessment was based on plain radiographs and Brantigan fusion criteria at 1, 6, 12 and 24 months after surgery. All patients completed the VAS and ODI at baseline through last follow-up.ResultsClinical results showed good pain resolution. VAS back demonstrated an average reduction over baseline of 50%, 57%, 71%, 77% at 3, 6, 12 and 24 months, respectively (p